Intoxication symptoms and health conditions of family farmers associated with the use of pesticides: a study conducted in Zona da Mata Mineira, Brazil (Research, Society and Development, 2022)
This study aimed to evaluate the association between the use of pesticides, symptoms of intoxication and health conditions of family farmers in the Mata Mineira area, Brazil. This is a cross-sectional study with 48 family farmers from a municipality in the Zona da Mata, Minas Gerais. A semi-structured questionnaire was applied to obtain demographic, socioeconomic information and characterization of the use of pesticides. Blood samples were collected from farmers for biochemical tests and evaluation of markers of exposure to pesticides. It was found that 75% of farmers used pesticides in food production, most of these products being extremely toxic. These farmers showed changes in plasma cholinesterase, erythrocyte cholinesterase and butyrylcholinesterase, markers of exposure to pesticides. There was an association between spraying for more than 4 hours/day and reporting of acute symptoms of intoxication, as well as between the use of pesticides and the presence of chronic non-communicable diseases. Multivariate analysis indicated that non-compliance with the period of re-entry into crops after the use of pesticides remained as an explanatory variable for lung disease. We infer that acute symptoms, as well as chronic non-communicable diseases reported by family farmers, may be associated with the use of pesticides.